2003
DOI: 10.4028/www.scientific.net/kem.254-256.919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Micro/Nano Particle Size on Cell Function and Morphology

Abstract: The cytotoxicity of micro/nano particles in Ti, TiO and carbon nanotube was investigated by in vitro biochemical analyses using human neutrophils. The particles smaller and larger than the neutrophils were used to determine the relationship between cell and particle size with respect to cytotoxicity. As the particle size decreased, the cell survival rate was decreased and, with the good corresponding relation to this, the value of lactate dehydrogenase (LDH), which is the indication of cell disruption, was inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 8 publications
2
23
0
1
Order By: Relevance
“…In spite of this economical and technological context, it is surprising that only very few studies have been published about their potential toxicity. The vast majority of the studies focusing on the impact of CNTs has been devoted to the study of the toxicity and immunotoxicity in in vitro cellular models on human or rat cells (Shvedova & Castranova 2003;Tamura et al 2004, see for review Smart et al 2006;Cui et al 2005;Jia et al 2005;Monteiro-Rivière et al 2005;Muller et al 2005;Salvador-Morales et al 2006 Smart et al (2006) indicated that in the last five years, disturbing and often conflicting data have emerged concerning the safety of CNTs. To our knowledge no information is currently available about the toxic effects of such materials in in vivo studies, except the following studies on aquatic organisms: (i) Freshwater crustaceans (Daphnia magna and Hyalella azteca ), a marine copepod and fish (Pimephales promelas and Oryzias latipes ) exposed to C60 (fullerenes) (Oberdö rster 2004a,b;Oberdörster et al 2006), (ii) on zebrafish embryos (Danio rerio ) exposed to SWNTs and DWNTs (Cheng et al 2007), (iii) on estuarine copepod (Amphiascus tenuiremis ) exposed to SWNTs (Templeton et al 2006) and (iv) on juvenile trout (Oncorhynchus mykiss) exposed to SWNTs (Smith et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this economical and technological context, it is surprising that only very few studies have been published about their potential toxicity. The vast majority of the studies focusing on the impact of CNTs has been devoted to the study of the toxicity and immunotoxicity in in vitro cellular models on human or rat cells (Shvedova & Castranova 2003;Tamura et al 2004, see for review Smart et al 2006;Cui et al 2005;Jia et al 2005;Monteiro-Rivière et al 2005;Muller et al 2005;Salvador-Morales et al 2006 Smart et al (2006) indicated that in the last five years, disturbing and often conflicting data have emerged concerning the safety of CNTs. To our knowledge no information is currently available about the toxic effects of such materials in in vivo studies, except the following studies on aquatic organisms: (i) Freshwater crustaceans (Daphnia magna and Hyalella azteca ), a marine copepod and fish (Pimephales promelas and Oryzias latipes ) exposed to C60 (fullerenes) (Oberdö rster 2004a,b;Oberdörster et al 2006), (ii) on zebrafish embryos (Danio rerio ) exposed to SWNTs and DWNTs (Cheng et al 2007), (iii) on estuarine copepod (Amphiascus tenuiremis ) exposed to SWNTs (Templeton et al 2006) and (iv) on juvenile trout (Oncorhynchus mykiss) exposed to SWNTs (Smith et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The modifications of CNTs have been extensively investigated because of their relevance in electrical, mechanical and biological applications [1][2][3][4][5][6][7][8]. Immobilization of various functional molecules on CNT has also been examined in past studies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…responses of cells treated with nanoparticles of other materials (Dick et al, 2003;Brown et al, 2004;Tamura et al, 2004;Geiser et al, 2005;Inoue et al, 2006;Lee et al, 2007;Rothen-Rutishauser et al, 2007;Waldman et al, 2007). Inoue et al (2006) studied the effects of two different sized (14 and 56 nm diameter) carbon nanoparticles on murine lung macrophage and found that the smaller (d = 14 nm) carbon nanoparticles induced more IL-2 and IL-10 compared with the larger (d = 56 nm) particles.…”
mentioning
confidence: 99%
“…The engulfment and the final intracellular location of the nano-and microparticles may be different, and will lead to diverse biological responses by the macrophages. Localization of nanoparticles inside the cell may ultimately play a role in the biological responses, whether located along the inner or outer membrane surface or outside of the cell membrane (Tamura et al, 2004;Rothen-Rutishauser et al, 2007). Tsoli et al (2005) demonstrated that gold nanoparticles localized in the vicinity of the cell nuclei and interacted with DNA, leading to pronounced toxicity.…”
mentioning
confidence: 99%